1996
DOI: 10.1111/j.1469-8137.1996.tb01907.x
|View full text |Cite
|
Sign up to set email alerts
|

Phragmites die–back: bud and root death, blockages within the aeration and vascular systems and the possible role of phytotoxins

Abstract: S I' M M h R YDie-back and healthy stands oi Phragmites australu (Cav.) Trin. ex Steud. in the UK and Hungary were compared in terms of stand architecture, plant morphology and anatomy, sediment redox potential and sulphide le\-els, plant resistance to internal Poiseuille gas flow, and convecti\-e flow characteristics of culms. Compared with healthy sites, die-back sites were characterized by lower sedmient redox potentials, and in Hungary by \-ery high sulphide levels. Plants at die-back sites showed a marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 33 publications
1
76
0
Order By: Relevance
“…The main factors regulating which of the two nitratereducing processes will be favored are the concentrations and ratios of available electron donors and acceptors [20,27]. Aerenchymatous plants create an oxic-anoxic interface in the root zone by releasing oxygen into this zone [2,22]. The release of oxygen by the roots may stimulate nitrification [5,9,19] and, subsequently, denitrification after diffusion of nitrate into the reduced zone of the sediment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors regulating which of the two nitratereducing processes will be favored are the concentrations and ratios of available electron donors and acceptors [20,27]. Aerenchymatous plants create an oxic-anoxic interface in the root zone by releasing oxygen into this zone [2,22]. The release of oxygen by the roots may stimulate nitrification [5,9,19] and, subsequently, denitrification after diffusion of nitrate into the reduced zone of the sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication could lead to anoxia in the below ground growing parts of P. australis because the increased litter production may result in an increase of decomposition activity in the sediment compartment. Also, it has been shown that at the die-back sites, aeration by plants was affected negatively due to blockages in the aerenchymatous tissue [2].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of die-back in reed beds include a clumped habit, stunting and death of shoots and roots, premature senescence, death of buds and rhizomes, impeded diffusive and convective aeration of the underground parts due to occlusions of callus, blockages within vascular systems and lignification and suberization of surface layers of laterals and apices of adventitious roots *Author for correspondence (fax 01482 465458 ; e-mail w.armstrong!biosci.hull.ac.uk). (Armstrong et al, 1996a ;Armstrong et al, 1996c,d ;Kohl et al, 1996 ;Rolletschek et al, 1998). Other symptoms include weakened culms (Klo$ tzli 1971 ;Sukopp et al, 1975 ;Sukopp & Markstein, 1989), altered ratios of various amino acids and ratios of amino acids : sugars in culm bases (Kohl & Henning, 1987 ;Kohl et al, 1998) and lower levels of starch in rhizomes (Cizkova et al, 1996b).…”
Section: mentioning
confidence: 99%
“…Growth of Phragmites can be poor when cultivated in sediments containing an organic layer of rotting rhizomes and roots of the plant (Armstrong et al, 1996c). Bud death and reed decline have been associated at Lake Ferto in Hungary with high levels of sulphide : up to 4 mM (128 ppm) (Armstrong et al, 1996a) and at Rozmberk West, an anthropogenically induced eutrophic site in the Czech Republic, with a strongly reducing organic layer in the surface of the lake sediment (Cizkova et al, 1996a) and with high levels of some organic acids in interstitial waters, including acetic (H. Cizkova, pers. comm.).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation